A case of church discipline in 1 Corinthians 5 - Gennadi SERGIENKO (Богословські роздуми: Східноєвропейський журнал богословʼя)
A case of immoral behavior at the church in Corinth threatened the reputation of the Christian community. The community itself, however, due to some theological and social factors, did not realize the seriousness of the threat. Most probably such behavior was perceived as an example of the new “spiritual” freedom of the believers. The situation might have been further complicated if the sinning brother was one of the influential patrons of the church. In trying to correct the situation, Paul points to the incompatibility of sin with the status of the Christian. In arguing his position, Paul creatively reapplies the Old Testament Scriptures to a qualitatively new situation. In so doing, he sets a precedent for ministers of the Word of our day.